2020
DOI: 10.3390/ma13214720
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced TiAl Alloy for High-Performance Racing Applications

Abstract: Requirements and strict regulations for high‑performance racing applications involve the use of new and innovative lightweight structural materials. Therefore, intermetallic γ‑TiAl-based alloys enable new opportunities in the field due to their lower density compared to commonly used Ni‑base superalloys. In this study, a β‑solidifying TiAl alloy was examined toward its use as structural material for inlet and outlet valves. The nominal composition of the investigated TNM alloy is Ti–43.5Al–4Nb–1Mo–0.1B (in at%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 70 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, the behavior of fatigue at the microscopic scale is dependent on the behavior of the microstructure under high temperatures. Both Burtscher et al 98 and Wu et al 33 have demonstrated that in Ti‐alloys with a high amount of Al (40%) the trueα2γ colonies and β , γ phases play a significant effect in the start and propagation orientation of cracks. The microstructure is mostly made up of trueα2γ lamellar colonies, as seen in Figure 17.…”
Section: Rbf Of Am'd Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the behavior of fatigue at the microscopic scale is dependent on the behavior of the microstructure under high temperatures. Both Burtscher et al 98 and Wu et al 33 have demonstrated that in Ti‐alloys with a high amount of Al (40%) the trueα2γ colonies and β , γ phases play a significant effect in the start and propagation orientation of cracks. The microstructure is mostly made up of trueα2γ lamellar colonies, as seen in Figure 17.…”
Section: Rbf Of Am'd Materialsmentioning
confidence: 99%
“…(A) Schematic of micro‐cracks initiation and propagation in the presence of trueα2γ colonies in Ti‐Al alloy (wrought) under RBF test in high temperature 98 ; (B) fracture surface of AM'd material under RBF test in room temperature (red circles are showing crack initiation from porosities) 79 . [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Rbf Of Am'd Materialsmentioning
confidence: 99%
“…This material can be found in modern airplane jet engines because of its resistance to high temperatures [10]. It is also used in high-performance vehicle engines [11]. This alloy material has excellent oxidation resistance and good structural stability during long-term thermal exposure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The turbine wheel in this product was cast TiAl alloy, which was manufactured by precision casting and joined to a low-alloy steel shaft to form the turbine rotor. Even in recent research on the practical application of TiAl alloys, small blades [2,3] and engine valves [4] manufactured by casting, isothermal forging, and extrusion are targeted, and there are no development examples of parts weighing 0.5 kg or more. The TiAl alloy is currently mostly used in the low-pressure turbine blades of jet engines [5] Parts manufactured by precision casting were initially used for practical applications; however, because the TiAl alloy is poorly castable, casting a near-net into a blade shape was difficult, with very large surplus materials required, leading to large amounts of machining that effectively negated the merits of precision casting.…”
Section: Introductionmentioning
confidence: 99%